Optimizing Restorative Justice as an Alternative to Overcoming Corporate Crime in Indonesia - Muksin, Muchlas Rastra Samara; Pujiyono, Pujiyono; Cahyaningtyas, Irma (Universitas Internasional Batam, 2025)
This research aims to analyze how the regulation of corporate criminal liability in Indonesia and the opportunity of restorative justice as an alternative to corporate crime prevention in Indonesia. By using a normative approach this research uses a case approach, statutory approach, philosophical approach and comparative approach, this research explores the regulation of corporate criminal liability in Indonesia and how the challenges of alternative corporate crime resolution through restorative justice as a means of crime prevention. The results of this study The legal framework in Indonesia has not been able to fully address the complexity of corporate criminal liability, both in terms of material and procedural aspects.The retributive approach has proven to not touch the root of the problem. This is where restorative justice offers an alternative with a focus on restoring relations between perpetrators, victims, and the community. However, its application in the corporate context is still limited and not supported by integrated regulations.Meanwhile, countries such as France and Germany have adopted the Victim Offender Mediation (VOM) mechanism as part of their criminal justice system. In France, VOM has a strong legal basis, including the 1993 amendment to the Criminal Procedure Code and institutional support from INAVEM. VOM is implemented at the pre prosecution stage, with the condition that the perpetrator admits guilt and the victim's consent. Judges and prosecutors are given the discretion to drop the case if mediation is successful.VOM there is not only a forum for compromise, but also a tool for restoring participatory and humane justice. With a clear mechanism and the active role of mediation institutions, this system opens up opportunities for renewal in handling corporate crimes in Indonesia.